INOVASI TEKNOLOGI HIDROPONIK BAGI MASYARAKAT DI NAGARI SUNGAI KUNYIT KABUPATEN SOLOK SELATAN - Ferry Lismanto Syaiful; Sri Winda Harni (Jurnal Hilirisasi IPTEKS, 2021)
Hydroponics is an innovation of plant cultivation without using soil as a growing medium. As a substitute for the medium, use a liquid nutritional mineral solution together with water or other materials containing nutrients such as coconut fiber, mineral fiber, sand, broken bricks, sawdust, and other materials to function as a medium. The objectives of this activity are: 1. increasing knowledge of farmers/breeders about technological innovations for horticultural crop cultivation, 2. increasing skills of farmers/breeders in the application of hydroponic technology in their environment, 3. seeding, planting, and maintaining horticultural crops with the application of good agricultural practice (GAP) with hydroponic technology, 4. utilization of home yardland in plant cultivation with hydroponic technology. This activity was carried out in village Sungai Kunyit, South Solok Regency. The method of activities carried out in the form of hydroponic socialization, question and answer discussions, and demonstrations of farming using hydroponic technology. The results of the activities obtained have succeeded in empowering the village Sungai Kunyit community, South Solok, and increasing their interest and knowledge in using home yard land to develop hydroponic technology cultivation. This work program can increase farmers' enthusiasm and can apply the practice of cultivating horticultural crops in their respective yards. From the activities carried out, it can be concluded that the community in Sungai Kunyit village, South Solok gave a positive response to the activities carried out, even valuable.